2009
DOI: 10.1007/s00213-009-1572-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of endocannabinoid modulation of conditioned responding evoked by a nicotine CS and the Pavlovian stimulus effects of CP 55,940 in adult male rats

Abstract: Rationale -The cannabinoid CB 1 receptor antagonist/inverse agonist rimonabant (SR 141716) has been shown to block reinforcing and rewarding effects of nicotine. Research has not investigated whether the cannabinoid system is involved in the interoceptive stimulus effects of nicotine functioning as a conditional stimulus (CS). Objective -We examined the effects of rimonabant and the CB 1/2 receptor agonist, CP 55,940, on responding evoked by a nicotine CS in rats. Additionally, we determined whether CP 55,940 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…A similar result was found by Polewan et al (2013) using a 0.4 mg/kg training dose. As in previous studies, stimulus control over conditioned responding was dose-dependent; higher doses of nicotine evoked increased goal-tracking relative to the lower doses (Besheer et al , 2004; Murray et al , 2007a, b; Murray et al , 2009c; Reichel et al , 2007; Reichel et al , 2010; Struthers et al , 2009). Further, mecamylamine dose-dependently blocked goal-tracking evoked by 0.2 and 0.1 mg/kg nicotine; as mecamylamine dose increased, goal-tracking decreased.…”
Section: Discussionsupporting
confidence: 68%
“…A similar result was found by Polewan et al (2013) using a 0.4 mg/kg training dose. As in previous studies, stimulus control over conditioned responding was dose-dependent; higher doses of nicotine evoked increased goal-tracking relative to the lower doses (Besheer et al , 2004; Murray et al , 2007a, b; Murray et al , 2009c; Reichel et al , 2007; Reichel et al , 2010; Struthers et al , 2009). Further, mecamylamine dose-dependently blocked goal-tracking evoked by 0.2 and 0.1 mg/kg nicotine; as mecamylamine dose increased, goal-tracking decreased.…”
Section: Discussionsupporting
confidence: 68%
“…As in our previous reports, rats in both experiments readily learned to goal-track when administered nicotine (Murray et al , 2009c; Struthers et al , 2009; Wilkinson et al , 2010). Following discrimination training, we examined the effects of early extinction with nornicotine or varenicline.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have shown that, when given to rats trained to detect the effects of nicotine, cannabinoid ligands do not have nicotine-like discriminative effects, nor do they alter the discriminative effects of nicotine when administered prior to nicotine [81,87,104]. However, opposite results have been obtained by Murray et al [105], who investigated endocannabinoid system involvement in the interoceptive effects of nicotine by using a Pavlovian discrimination procedure that differs from the drug-discrimination procedure described above. In this procedure the intermittent delivery of water occurred only during sessions when rats received nicotine; no operant response was required to produce the water, but the number of times the rat placed its head into the water dipper was measured.…”
Section: Cb 1 Receptors and Nicotine's Subjective Effectsmentioning
confidence: 87%